Cinnamon Tea As A Therapeutic Intervention For Type-2 Diabetes Patients (The Review of Diabetic Studies, 2025)
According to new national estimates for diabetes, there were 101 million diabetics and 136 million prediabetics in India by 2021. Between 2019 and 2021, 31 million Indians developed diabetes. The present study evaluated the effect of cinnamon tea on type 2 DM by utilizing the experimental quantitative approach with a pre-test-post-test-control group design with a non-probability, purposive sampling technique. A total of 104 participants, i.e., 52 experimental and 52 control, were selected from the community area (stratum) according to the selection criteria.Results showed that in the current investigation, the experimental group, following intervention with cinnamon tea, exhibited a significant difference in post-interventional blood sugar levels (p-value = 0.0001). The average PPBSL on day 8 was compared between the experimental and control groups using an unpaired t-test. On day 8, the mean PP BSL in the experimental group was 187.31 with a standard deviation of 14.51, while in the control group, it was 203.63 with a standard deviation of 11.91. The unpaired t-test statistic result was -5.54155, with a p-value of 0.000064. It indicates a significant difference in the average PPBSL on day 8 between the experimental and control groups at the 5% level of significance. As a result, H0 was rejected, and H1 was accepted.The findings reveal that cinnamon tea is more effective in decreasing the blood sugar levels in type 2 diabetes patients.